2013
DOI: 10.1186/1532-429x-15-15
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal strain from velocity encoded cardiovascular magnetic resonance: a validation study

Abstract: BackgroundRegional myocardial function is typically evaluated by visual assessment by experienced users, or by methods requiring substantial post processing time. Visual assessment is subjective and not quantitative. Therefore, the purpose of this study is to develop and validate a simple method to derive quantitative measures of regional wall function from velocity encoded Cardiovascular Magnetic Resonance (CMR), and provide associated normal values for longitudinal strain.MethodBoth fast field echo (FFE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The clinical utility found in Peru of 56% having changed care after CMR is somewhat less than demonstrated in international registries, as European/US registries have reported that CMR changed care in 61.8% of patients 30, 31. However, we would have reached these levels in our study by including the 5% of patients in which a change in management was appropriate but not possible due to access barriers.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The clinical utility found in Peru of 56% having changed care after CMR is somewhat less than demonstrated in international registries, as European/US registries have reported that CMR changed care in 61.8% of patients 30, 31. However, we would have reached these levels in our study by including the 5% of patients in which a change in management was appropriate but not possible due to access barriers.…”
Section: Discussionmentioning
confidence: 56%
“…Quality: The rapid CMR protocol was tested in advance using freely available video conferencing software. We used low‐dose gadolinium (0.1 mmol/L per kg) for cost and so the blood‐pool was not bright at the time of LGE imaging 33. The CMR studies were conducted within a safe environment, with only one minor complication which was a panic attack.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of LGE has been rarely reported in previous studies evaluating smaller cohorts and case reports of patients with sickle cell disease 12-16 . Notably, the significant proportion of patients with LGE is a novel finding in patients with SCD.…”
Section: Discussionmentioning
confidence: 88%
“…Despite its recognised advantages, CMR has significant limitations in quantifying myocardial deformation (eg, myocardial strain). While specific techniques such as tissue-tagging CMR or harmonic phase analysis have been available to this end, their acceptance has been limited due to the requirement for sophisticated and time-consuming sequence acquisition, need for specific expertise and financial reasons 16. The introduction of CMR feature tracking (FT)—a technique allowing the quantification of myocardial strain using standard cine steady-state free-precession sequences—offers the opportunity to quantify myocardial deformation directly without resorting to echocardiography 17.…”
Section: Introductionmentioning
confidence: 99%